Princípios limitadores da prevenção especial positiva da pena privativa de liberdade - Suliani, Paulo Ricardo (2012)
Considering the evident lack of effectiveness and legitimacy of the widely disseminated idea of rehabilitation through punishment, this dissertation analyzes the concepts that intend to justify the existence and purposes of prison as a form of punishment through the principles that guide the current State (democratic, secular, legal, Republican), as well as through the elements of international recognition of citizenship (dignity, freedom, autonomy of conscience), and also taking into consideration principles that enable the construction of a humanist Criminal Law. Reaching for a special kind of prevention, known as positive special prevention , one can verify that in reality there are excesses in the application of the prison punishment, and therefore this work seeks to find conditions that, even though still ideal, would allow actual rehabilitation to happen. This dissertation offers a critical, current, democratic view on the various notions of punishment, particularly on those which seem to be legitimized due to a rehabilitation speech, in order to build an alternative that may agree with the founding principles of a Democratic State.